Growth or stagnation? : a review of Bangladesh's development, 1996. - Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press Ltd., 1997)
Contributed articles.
Includes bibliographical references.
BIED
Complimentary copy from BIED, Donated By Akbar Ali Khan
Keywords: Rural poor -- Bangladesh; Economics; Bangladesh -- Economic policy; Bangladesh -- Economic conditions